The psychological impact of the COVID-19 crisis on young Swiss men participating in a cohort study (Swiss Medical Weekly, 2021)
AIMS:The COVID-19 pandemic caused many disturbances to daily life worldwide and may also have significantly affected people’s psychological well-being. The present study aimed to describe the psychological impact of the crisis on our sample of young Swiss men and to examine differences due to their linguistic region, experiencing COVID-19 symptoms and living arrangements.METHODS:Based on an ongoing cohort study, we assessed a general-population sample of young Swiss men (n = 2345; average 29 years old) shortly before (from April 2019) and early on during the COVID-19 crisis (between 13 May and 8 June 2020). This was a unique opportunity to estimate the crisis’ psychological impact in the form of depression, perceived stress and sleep quality (assessed before and during COVID-19), and any crisis-induced fears, isolation or psychological trauma. Associations of psychological impact with living arrangements, experiencing COVID-19 symptoms and linguistic region (German-speaking vs French-speaking) were investigated using linear regression models. FINDINGS:By the time participants responded to our questionnaire, less than 1% had been tested positive for COVID-19, 2.6% had been tested negative and 14.7% had had some COVID-19 symptoms but had not been tested. About 8.2% of the sample reported at least some symptoms of psychological trauma (≥24 points on the Impact of Event Scale). On average, participants reported higher levels of fear for others (43.6% at least moderate) and economic fear (12.7% at least moderate) than fear for themselves (5.8% at least moderate). Those living alone and those who reported having COVID-19 symptoms themselves, or knowing someone with symptoms, reported higher overall psychological impact in the form of depression, perceived stress, sleep quality, psychological trauma, fear and isolation. Associations with linguistic region varied by outcome, with higher levels of depression and fear in French-speaking regions and higher levels of perceived stress and isolation in German-speaking regions. INTERPRETATION:The crisis had a considerable impact on the psychological well-being of our sample of young Swiss men, and some groups were more affected than others: those living alone and those who had shown COVID-19 symptoms themselves or had known someone with symptoms may have felt a greater psychological impact from the crisis. Supporting those at a higher risk of psychological consequences in such crises, whether through structural measures or via individual support, should be an important aspect of crisis management and could help reduce the overall impact of the current pandemic on Switzerland’s population.